Implementasi Nilai-Nilai Bhineka Tunggal Ika Pada Mahasiswa Angkatan 2022 Prodi PPKn UNIPA Surabaya - Suyono Suyono (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Bhineka Tunggal Ika is one of the four pillars of Indonesian nationalism, a reminder that diversity is a source of strength and wealth for the nation, and must be preserved. The values of Bhineka Tunggal Ika are important to maintain social harmony and unity. The purpose of writing this article is to observe the implementation of Bhineka Tunggal Ika values in college schools. The research subjects were students of the Class of 2022 of the PPKn study program at Unipa Surabaya. This research aims to explore and apply the values of Bhineka Tunggal Ika to students as an effort to strengthen harmony and diversity in the college environment. Bhineka Tunggal Ika, which means "Different but still one," is the spirit of diversity that is the foundation for the life of the nation and state in Indonesia. This research uses qualitative methods to collect data from students who represent diverse cultural, religious and ethnic backgrounds. Through interviews, observations, and documentation studies. This research will identify the perception, understanding, and implementation of Bhineka Tunggal Ika values in students' daily lives. The implementation of the values of diversity is expected to create an inclusive campus environment that respects diversity, as well as make a positive contribution to the character building of students as prospective national leaders with superior personalities.